MP35: Targeting the opioid crisis by influencing opioid prescribing in the emergency department. (May 2020) - Shelton, D.; Teo, V.; Ding, K.; Hefferon, D.
Abstract : Background: Liberal prescribing of opioids is a major contributing factor to the opioid crisis. Patients who take opioids for >5 consecutive days are at greater risk of long-term use. Evidence shows that significantly more opioids are prescribed for emergency department (ED) patients with acute pain compared to amounts consumed. Guidelines recommend prescribing a 3-day supply or 10-15 tablets of opioids for patients with acute pain Aim Statement: By January 2020, >70% of opioid prescriptions from our ED will be for <15 tablets of morphine 5 mg equivalents. Measures & Design: Emergency physicians were educated on best practice of prescribing opioids for discharged patients. An electronic prescription writer was built for discharged ED patients with a pop-up reminder for quantities >15 tablets (indicating a recommended quantity of 10-15 tablets) and a pop-up reminder for quantities >30 tablets (indicating a maximum quantity of 30 tablets and recommended quantity). A feature was built to auto-populate a prescription for morphine 5 mg po q4h prn x 10 tablets to facilitate adherence to guidelines. Outcome Measure % opioid prescriptions for <15 tablets of morphine 5 mg equivalents Process Measure Amount of opioids prescribed for discharged ED patients, measured as morphine 5 mg equivalents Number of opioid prescriptions for >30 tablets of morphine 5 mg equivalents Balancing Measure Number of patients that return to ED within 7 days and receive a repeat opioid prescription. Evaluation/Results: Prior to implementation of the electronic prescription writer a sample audit revealed that 50% of opioid prescriptions were written for <15 tablets of morphine 5 mg equivalents. For the first three quarters of 2019, 62%, 61% and 69% of opioid prescriptions were written for <15 tablets of morphine 5 mg equivalents. Only two prescriptions during the study period were for >30 tablets of morphine 5 mg equivalents. An average number of 7 patients per quarter were given a repeat opioid prescription during a return ED visit. Discussion/Impact: We were successful in influencing emergency physicians to prescribe fewer opioids to discharged patients. This has the potential to avoid converting ED patients with acute pain into long-term opioid users and to avoid the diversion of unused opioid tablets.